Considering the Influence of Digital Promotion Performed By Go-Jek Indonesia and C2C Marketplaces on Buyers’ Purchasing Decision - ., Tusyanah; Maftukhah, I; Dyah Rahmawati, F; Fadlilah, A (KnE Social Sciences, 2018)
Ayuwuragil (2018) stated that there are only 3.89 million or about 8 percent of the 59.2 million small and medium enterprises (SMEs) in Indonesia are utilizing the digital platform [4]. This digital platform actually is a golden opportunity for SMEs to develop their businesses. Thus; we need to study whether GO-JEK Indonesia and C2C marketplaces have really helped SMEs in promoting which ultimately increase the sales of their products. The purpose of this study is to determine the influence of digital promotion performed by GO-JEK Indonesia and C2C marketplaces on product purchasing decision. It was a quantitative study which took 200 respondents taken by purposive random sampling from 700 students as the population. They were selected if they did purchase at GO-JEK Indonesia and C2C marketplaces. The data were collected through questionnaires and documentation, and then, analyzed by descriptive statistics and multiple regressions analysis. The results showed that the regression equation is Y = 12.470 + 0.553X1 + 0.272 X2 + e. then, it also shows that: 1) partially, digital promotion performed by GO-JEK Indonesia gives influence on product purchasing decision for 13.39percent; 2) partially, digital promotion performed by C2C marketplaces gives influence on product purchasing decision for 4.41percent, 3) and simultaneously, digital promotion performed by GO-JEK Indonesia and C2C marketplaces gives influence up to 24.5percent. The respondents were students; they said that they purchased more products on GO-FOOD of GO-JEK Indonesia than marketplaces. It happens because of their needs and financial capacity. Keywords: digital promotion, C2C marketplaces, GO-JEK Indonesia, buyers’ purchase decision